2022
DOI: 10.1159/000522274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acceptance and Commitment Therapy in Daily Life in Early Psychosis: Results from the Multi-Center INTERACT Randomized Controlled Trial

Abstract: <b><i>Introduction/Objective:</i></b> This study aimed to investigate efficacy of Acceptance and Commitment Therapy in Daily Life (ACT-DL), combining face-to-face therapy with an Ecological Momentary Intervention (EMI), in addition to treatment as usual (TAU) for psychotic distress, in comparison to TAU. <i>Methods</i>: Individuals aged 15–65 years with clinically established ultra-high risk or first episode of psychosis were randomly assigned to TAU or ACT-DL+TAU. ACT-DL+TA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…This has clearly been an obstacle to the dissemination and uptake of ACTp internationally relative to other evidence‐based therapies commonly offered to those with psychosis, such as CBTp and family interventions. This is despite evidence that ACT is a model showing cross‐cultural validity with many intervention studies conducted in non‐English speaking, low‐ and middle‐income countries (Association for Contextual Behavioral Science, 2023), and ACTp studies involving diverse samples in multiple countries and regions (e.g., Gaudiano & Herbert, 2006; Jeong et al, 2022; Johns et al, 2016; Jolley et al, 2020; Myin‐Germeys et al, 2022; Shi et al, 2023). ACTp has only recently begun to find its way into clinical practice guidelines as an evidence‐based treatment and much more work is needed to assemble all the pieces of research necessary to support strong recommendations for its use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has clearly been an obstacle to the dissemination and uptake of ACTp internationally relative to other evidence‐based therapies commonly offered to those with psychosis, such as CBTp and family interventions. This is despite evidence that ACT is a model showing cross‐cultural validity with many intervention studies conducted in non‐English speaking, low‐ and middle‐income countries (Association for Contextual Behavioral Science, 2023), and ACTp studies involving diverse samples in multiple countries and regions (e.g., Gaudiano & Herbert, 2006; Jeong et al, 2022; Johns et al, 2016; Jolley et al, 2020; Myin‐Germeys et al, 2022; Shi et al, 2023). ACTp has only recently begun to find its way into clinical practice guidelines as an evidence‐based treatment and much more work is needed to assemble all the pieces of research necessary to support strong recommendations for its use.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Vilardaga et al (2020) reported that individuals with severe mental illness including psychosis ( n = 62) randomised to a mobile health app that included ACTp strategies showed reduced daily cigarette consumption compared with those receiving a standard smoking cessation app. Also, a study for people with early psychosis ( n = 148) reported that those randomised to ACT in Daily Life, which combined traditional therapy with a mobile intervention, produced greater improvements in global functioning, negative symptoms and momentary psychotic symptom distress compared with treatment as usual (Myin‐Germeys et al, 2022). Additionally, Wood et al (2021) described the implementation of a four‐session ACTp group for first episode psychosis patients delivered via telehealth, which had high adherence and client satisfaction.…”
Section: Lingering Questionsmentioning
confidence: 99%
“…Recruitment procedure and inclusion criteria for INTERACT have been described in detail elsewhere (Myin-Germeys et al, 2022). In Interviews were performed after verbal and written explanation and after written informed consent of the participant.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Therefore, 'ACT in Daily Life' (ACT-DL) was developed, a blended care intervention combining ACT-sessions with an app to add Ecological Momentary Intervention (Myin-Germeys et al, 2016) to enhance therapeutic effects in real life conditions in early psychosis (Vaessen et al, 2019). The INTERACT study (Myin-Germeys et al, 2022) quantitatively investigated ACT-DL and showed that adding ACT-DL to treatment as usual (TAU) significantly improved momentary psychotic distress, global functioning, and negative symptomatology, compared to only TAU, for participants with UHR and FEP.…”
mentioning
confidence: 99%
“…We developed the app to augment the effects of the therapy in patients in the early phases of psychosis (11). In a randomized controlled trial, we found that ACT-DL was outperforming treatment-as-usual (including CBT) in improving negative symptoms and social functioning, two of the hardest-to-treat symptoms (12). Furthermore, we found that the intervention was feasible and accessible although it could further be optimized for use in this patient group (13).…”
Section: Guest Editorialmentioning
confidence: 99%